Comparison of clinical outcomes in patients with congenital anorectal malformation treated with posterior sagittal anorectoplasty and laparoscopically assisted anorectal pull through - Kunnur, Vijaymahantesh S; Singh, Chandra Shekhar; Kunnur, Shanthala V; Kunnur, Anil Kumar S (Indian Journal of Child Health, 2016)
Aim: To compare the complications and outcomes of laparoscopic-assisted anorectoplasty (LAARP) for anorectal malformation (ARM) with that of posterior sagittal anorectoplasty (PSARP) using Kelly’s score. Materials and Methods: This was a single-center study conducted over a period of 4-year. A total of 95 male ARM patients were included in the study, of which 25 patients underwent LAARP, whereas 70 patients underwent PSARP. Result: Superficial wound infection was seen in 2 (2.85%) cases of the PSARP group while in 1 (4%) case in LAARP group. 12 (17.14%) cases of PSARP group had wound dehiscence at the neo-anal site, of which 6 (8.57%) had complete wound dehiscence and the remaining 6 (8.57%) had partial dehiscence, whereas 4 (16%) cases had wound dehiscence in LAARP group of which 3 (12%) had partial and 1 (4%) had complete dehiscence. Retraction of the neo-anus was seen in 6 (8.57%) cases of PSARP group while in 2 (8%) cases of LAARP group. Ectopically placed neo-anus was seen in 3 (4.28%) patients of PSARP group while in none of the cases in LAARP group. None of the patients in LAARP group had anal stenosis, whereas 2 (2.85%) patients underwent redoanoplasty in PSARP group for anal stenosis. Mucosal prolapse was seen in 8 (11.42%) cases of PSARP group, as compared to 3 (12%) patients of LAARP group. The net average Kelly’s score in LAARP group was 4.56, whereas, in PSARP group, it was 4.10. Conclusion: This study emphasizes the emerging laparoscopic technique for the management of ARMs. Using this approach, it is possible to achieve better continence rates as the extent of perineal dissection is minimal.